High prevalence of human immunodeficiency virus, hepatitis B and C viral infections among people who inject drugs: a potential stumbling block in the control of HIV and viral hepatitis in Tanzania - Rahim H. Kawambwa; Mtebe V. Majigo; Ahmed A. Mohamed; Mecky I. Matee (BMC, 2020)
Abstract Background Tanzania has witnessed a significant decrease in the prevalence of human immunodeficiency virus (HIV) and viral hepatitis in the general population attributed to several interventional measures. It is uncertain whether this decline has also occurred among people who inject drugs (PWID). This study aimed to determine the seroprevalence of HIV, Hepatitis B and C viruses infection among PWID recruited from their hotspot sites in Dar es Salaam, Tanzania. Methods A cross-sectional study conducted between June and September 2017 recruited PWID from pre-identified hotspot sites using a snowball referral sampling technique. A structured questionnaire was used to obtain information regarding socio-demographic characteristics, behaviour and drug use. Blood was tested for the presence of IgG antibodies against HIV and Hepatitis C virus (HCV) and hepatitis B surface antigen (HBsAg). Data were entered in the computer using excel software and analysed using Statistical Package for Social Sciences version 20. Results A total of 219 PWID were recruited, the majority of whom were males (74.9%), unmarried (60.7%), had low education (62.6%) and low income (57.1%). The median age was 39 years, with an inter-quartile range of 35-43. Approximately 32.0% had a history of drug injection for more than 3 years, 79.9% were injecting drugs more than 3 times per day and 47.5% were sharing needles. The overall prevalence of HIV, HBsAg, and HCV was 33.8, 7.8, and 50.2%, respectively. There was serologic evidence of at least one infection for 68.9%, while 22.4% had two or more infections. HIV infection was independently associated with being married, while HCV was associated with injecting drugs for more than 3 years and unprotected sex. Conclusion Over two-third of PWID had serologic evidence of infection with at least one virus while 22.4% having at least two infections. The high prevalence of HIV and viral hepatitis infections among PWID may hamper initiatives of ending HIV and viral hepatitis epidemics in Tanzania.